Summer mortality of the Pacific cupped oyster Crassostrea gigas in the Bay of Marennes-Oleron (France). Spatial variability of environmental parameters, growth and production rates using a Geographical Information System (GIS) - Soletchnik, Patrick; Le Moine, Olivier; Razet, Daniel; Geairon, Philippe; Faury, Nicole; Goulletquer, Philippe; Robert, Stephane (Journées Conchylicoles Ifremer 1999, 1999)
The Marennes-Oleron Bay is the first rearing area in Europe for the cupped oyster, with 35 000 tons proudced on a yearly basis. This species has suffered several chronic summer mortalities for the last 10 years.